Burnout syndrome in medicine students at a federal university in São Paulo - Maso Nassar, Leonardo (2022)
Burnout Syndrome is a psychological condition that affects mainly health professionals, including physicians, and can begin during the student's graduation period. The study aimed to analyze the Burnout Syndrome in students of a medical course of a federal university in the state of São Paulo. 94 students were interviewed between the 1st and 4th year of the medical course using the Maslach Burnout Inventory - Student Survey (MBI-SS) questionnaire. The questionnaire collection consisted of 15 questions that are subdivided into three subscales: Emotional Exhaustion (EE) (5 items); Disbelief (DE) (4 items) and Professional Effectiveness (PE) (6 items). Of the sample, 23.4% (n = 22) of the students fit the Burnout three-dimensional diagnostic criterion. The pedagogical didactic structure used in the course may have an influence on the students’ Burnout results, explaining the comparative differences with other studies.